Low-odor soft TPE composite material and preparation method thereof
By adding new odor deodorants, hindered amine-type light stabilizers and bio-based plasticizers to TPE materials, the aging problems caused by odor and ultraviolet irradiation during the thermal processing of TPE materials are solved, and low odor and weather resistance are achieved and improve environmental performance.
Patent Information
- Application Number
- CN202411791108.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-18
AI Technical Summary
Existing TPE materials produce unpleasant odors during thermal processing and are susceptible to ultraviolet irradiation, causing yellowing and aging, affecting the quality and service life of the product.
By adding new deodorants to capture, adsorb and degrade odor molecules, the UV shielding effect of the material is improved by using hindered amine-type light stabilizers and UV absorbers, and bio-based plasticizers are used to reduce the burden on the environment.
It significantly reduces the odor of the product, provides a more comfortable user experience, enhances the weather resistance and color stability of the material, while reducing the burden on the environment.
Smart Images

Figure BDA0005175331420000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of TPE composite materials, and in particular to a low-odor soft TPE composite material and a preparation method thereof. Background Art
[0002] Thermoplastic elastomer (TPE) is a type of polymer material that exhibits rubber elasticity at room temperature and can be plasticized and formed at high temperatures. Due to its unique physical properties and processing convenience, TPE is widely used in manufacturing fields such as medical devices, automotive interiors, and children's toys. However, during the thermal processing of TPE, due to the effects of high temperature and mechanical shear force, some molecular chains inside the material may break, producing low-molecular volatiles, which will release unpleasant odors and affect product quality and user experience. In addition, when used outdoors, traditional TPE materials are easily exposed to ultraviolet rays and cause yellowing and aging, affecting the appearance and service life of the product.
[0003] In order to reduce the odor of TPE materials, traditional methods usually use fragrances to cover it up, or use physical adsorbents such as activated carbon to absorb the odor, but these methods cannot fundamentally solve the problem because the product still contains odor molecules. At the same time, in order to improve the weather resistance of TPE, light stabilizers and antioxidants are usually added, but the selection and use of these additives need to be precisely controlled to ensure material performance while not burdening the environment.
[0004] With the improvement of environmental awareness and the increase in health and safety requirements, the market demand for low-odor, high-weather-resistant, and environmentally friendly TPE materials is growing. Therefore, the development of a new type of low-odor soft TPE composite material that can not only meet the low-odor requirements during processing and use, but also provide excellent weather resistance and environmental protection performance has become an important research direction in the field of materials science. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a low-odor soft TPE composite material and a preparation method thereof. The composite material of the present invention effectively captures, adsorbs and degrades the odor molecules generated during the hot melting process by adding a new deodorant, significantly reduces the odor of the product, and provides a more comfortable user experience. At the same time, the present invention improves the shielding effect of the material against ultraviolet rays by adding a hindered amine type light stabilizer and an ultraviolet absorber, and enhances the weather resistance and color stability of the product when used outdoors. In addition, the bio-based plasticizer used in the present invention is biodegradable, reducing the burden on the environment.
[0006] In order to achieve the above-mentioned object, the present invention provides a low-odor soft TPE composite material, which comprises, by weight, 50-100 parts of TPE thermoplastic elastomer, 5-20 parts of deodorant, 150-600 parts of plasticizer, 1-10 parts of antioxidant, 1-5 parts of light stabilizer, 0-20 parts of calcium stearate, 2-10 parts of nano silicon dioxide, 1-5 parts of organic silicon modifier, 50-150 parts of bio-based plasticizer, 1-5 parts of nano titanium dioxide, 0.1-1 parts of graphene nanosheets, 1-5 parts of metal organic framework compounds; 0.01-0.5 parts of carbon nanotubes, 0.5-2 parts of self-repairing polymer containing microcapsules, and 1-10 parts of antibacterial agents.
[0007] Preferably, the TPE thermoplastic elastomer is selected from one or more of hydrogenated SBS, SEBS, and SEPS;
[0008] The deodorant is a composite deodorant selected from one or more of nano-grade activated carbon, natural zeolite and bamboo charcoal powder.
[0009] Preferably, the antioxidant is selected from one or more of primary antioxidants, hindered phenol antioxidants, phosphite antioxidants, and vitamin E derivatives.
[0010] Preferably, the light stabilizer is selected from one or more of hindered amine light stabilizers and benzophenone ultraviolet absorbers; and the plasticizer is cycloalkane white oil.
[0011] Preferably, the organosilicon modifier is selected from one or more of polydimethylsiloxane, silicone rubber, silicone oil, and silicone resin; the bio-based plasticizer includes one or more selected from citrate plasticizers, vegetable oil-based plasticizers, polylactic acid-based plasticizers, and starch-based plasticizers.
[0012] Preferably, the metal organic framework compound is selected from one or more of zinc-containing MOFs, copper-containing MOFs, iron-containing MOFs, aluminum-containing MOFs, and MOFs containing organic ligands.
[0013] Preferably, the self-healing polymer containing microcapsules is selected from one or more of thermosetting resin-based self-healing polymers, thermoplastic plastic-based self-healing polymers, shape memory polymer-based self-healing polymers, hydrogel-based self-healing polymers, photosensitive self-healing polymers, magnetosensitive self-healing polymers, pH-sensitive self-healing polymers, enzyme-catalyzed self-healing polymers, microvascular network self-healing polymers, and multilayer microcapsule self-healing polymers.
[0014] Preferably, the antibacterial agent is selected from one or more of silver ion compounds, copper ion compounds, zinc ion compounds, quaternary ammonium salt compounds, nano silver particles, and natural antibacterial agents, wherein the natural antibacterial agent is selected from tea tree oil or lavender oil.
[0015] The present invention also provides a method for preparing a low-odor soft TPE composite material, comprising the following steps:
[0016] Place TPE thermoplastic elastomer, deodorant, antioxidant, light stabilizer, calcium stearate, nano-silicon dioxide, silicone modifier, bio-based plasticizer, nano-titanium dioxide, graphene nanosheets, metal organic framework, carbon nanotube, self-healing polymer containing microcapsules and antibacterial agent in a container, add plasticizer, fully soak and swell for 24 hours; stir and blend evenly to obtain a composite material; pass the obtained composite material through an extruder or injection molding machine at 140-200°C to make a hot-melt fluid, and send it into a molding cavity, and obtain a substrate or a product after cooling.
[0017] The technical solution of the present invention has the following beneficial effects:
[0018] The deodorant of the present invention has good performance in capturing, adsorbing and degrading odor molecules generated during the hot melting process of the TPE compound material; the heat-stable antioxidant inhibits the degradation reaction performance of the molecular chain breakage, cross-linking and other degradation reactions of the TPE compound material, thereby enhancing the thermal oxidative decomposition of the compound material during the preparation process and the environmental weather resistance, thereby preventing further odor from occurring; the light stabilizer has weather resistance to environmental light aging of the formed product.
[0019] Therefore, the composite material formed by the compound blending of the present invention has good heat resistance, low odor, and ultraviolet weather resistance, and the processing method is as simple as the traditional process.
[0020] The deodorants selected in the present invention are based on materials that can capture, adsorb and degrade odor molecules. These deodorants effectively reduce volatile organic compounds (VOCs) and other odor molecules generated by thermal decomposition during the hot melting process of the TPE composite material through physical adsorption and chemical decomposition. The selection and dosage of the deodorant are carefully designed to ensure that the odor is minimized without compromising the performance of the TPE matrix.
[0021] The addition of the heat-stable antioxidants of the present invention is to inhibit the thermal oxidation degradation of the TPE composite material during high-temperature processing. These antioxidants can interrupt free radical chain reactions, reduce molecular chain breakage and cross-linking, thereby reducing odors caused by thermal oxidation and improving the thermal stability and weather resistance of the material.
[0022] The light stabilizer of the present invention is added to protect the TPE composite material from aging caused by ultraviolet rays and other environmental factors. Hindered amine light stabilizers (HALS) and ultraviolet absorbers can absorb ultraviolet radiation and convert it into lower energy heat, reducing the photodegradation of the material caused by ultraviolet rays, thereby extending the service life of the material.
[0023] The use of the bio-based plasticizers of the present invention is to reduce the impact on the environment. These plasticizers are derived from renewable resources, such as vegetable oils or plant extracts. They are not only biodegradable, but also reduce the dependence on petroleum-based products to a certain extent, meeting the requirements of sustainable development.
[0024] The addition of nano silicon dioxide and graphene nanosheets in the present invention is to improve the hardness and wear resistance of the TPE composite material. Due to their high specific surface area and unique physical and chemical properties, these nano materials can form a reinforced network structure in the TPE matrix, thereby improving the overall performance of the material.
[0025] Adsorption properties of metal organic frameworks (MOFs): MOFs were introduced to enhance the adsorption capacity of composite materials for odor molecules and other small molecules by utilizing their high specific surface area and pore structure. MOFs can adsorb and store gas molecules at the molecular level, thus further improving the deodorization effect of the material.
[0026] The composite material of the present invention is designed with the same processing technology as traditional TPE materials in mind, which means that existing hot melt processing equipment and processes can be used to form the composite material of the present invention without large-scale transformation of the production line, thereby ensuring the convenience and economy of processing. DETAILED DESCRIPTION
[0027] The present invention is further described below in conjunction with specific embodiments.
[0028] Embodiment 1:
[0029] This embodiment provides a medical glove made of a low-odor soft TPE composite material, which is formulated according to the following components by weight:
[0030] TPE thermoplastic elastomer: 60 parts of hydrogenated SBS, 40 parts of SEBS;
[0031] Deodorant: 10 parts of nano-grade activated carbon, 5 parts of natural zeolite, 5 parts of bamboo charcoal powder;
[0032] Plasticizer: 400 parts of cycloparaffin white oil;
[0033] Antioxidants: 5 parts of hindered phenol antioxidant, 3 parts of phosphite antioxidant, 2 parts of vitamin E derivative;
[0034] Light stabilizer: 3 parts of hindered amine light stabilizer, 2 parts of benzophenone ultraviolet absorber;
[0035] Calcium stearate: 10 parts;
[0036] Nano silicon dioxide: 5 parts;
[0037] Silicone modifier: 3 parts of polydimethylsiloxane;
[0038] Bio-based plasticizer: 100 parts of citrate plasticizer;
[0039] Nano titanium dioxide: 3 parts;
[0040] Graphene nanosheets: 0.5 parts;
[0041] Metal organic framework compounds: 3 parts of zinc MOFs;
[0042] Carbon nanotubes: 0.1 parts;
[0043] Self-healing polymer containing microcapsules: 1 part of thermosetting resin-based self-healing polymer;
[0044] Antibacterial agent: 8 parts of silver ion compound;
[0045] Preparation steps:
[0046] After weighing all the raw materials according to the above ratio, place them in a high-speed mixer and mix them for 24 hours;
[0047] The uniformly mixed composite material is melt-blended through a twin-screw extruder, and the temperature of the extruder is set at 165°C;
[0048] The hot molten fluid at the outlet of the extruder is fed into the injection molding machine, and the injection molding machine injects the fluid into the molding mold cavity at 160°C;
[0049] Cooling the mold to solidify the hot molten fluid into a shape, and then demolding to obtain the medical glove substrate;
[0050] The obtained substrate is post-processed, such as trimming, grinding, etc., to meet the requirements of the final product.
[0051] Embodiment 2:
[0052] This embodiment provides a children's toy made of a low-odor soft TPE composite material, which is formulated according to the following weight components:
[0053] TPE thermoplastic elastomer: SEPS 70 parts;
[0054] Deodorant: 8 parts of nano-grade activated carbon, 7 parts of natural zeolite, 5 parts of bamboo charcoal powder;
[0055] Plasticizer: 500 parts of cycloparaffin white oil;
[0056] Antioxidant: 6 parts of hindered phenol antioxidant, 4 parts of phosphite antioxidant;
[0057] Light stabilizer: 4 parts of hindered amine light stabilizer, 3 parts of benzophenone ultraviolet absorber, 15 parts of calcium stearate;
[0058] Nano silicon dioxide: 8 parts;
[0059] Silicone modifier: 4 parts of silicone rubber;
[0060] Bio-based plasticizer: 120 parts of vegetable oil-based plasticizer
[0061] Nano titanium dioxide: 4 parts;
[0062] Graphene nanosheets: 0.8 parts;
[0063] Metal organic framework compounds: 4 parts of copper-containing MOFs;
[0064] Carbon nanotubes: 0.3 parts;
[0065] Self-healing polymer containing microcapsules: 1.5 parts of thermoplastic-based self-healing polymer;
[0066] Antibacterial agent: 6 parts of nanosilver particles;
[0067] Preparation steps:
[0068] After weighing all the raw materials according to the above ratio, place them in a high-speed mixer and mix them for 24 hours;
[0069] The uniformly mixed composite material is melt-blended through a twin-screw extruder, and the temperature of the extruder is set at 170°C;
[0070] The hot molten fluid at the outlet of the extruder is fed into the injection molding machine, and the injection molding machine injects the fluid into the molding mold cavity at 170°C;
[0071] Cooling the mold to solidify the hot molten fluid into a shape, and then demolding to obtain the children's toy substrate;
[0072] The obtained substrate is post-processed, such as trimming, grinding, etc., to meet the requirements of the final product.
[0073] Embodiment 3:
[0074] This embodiment provides a door and window sealing strip made of a low-odor soft TPE composite material, which is prepared according to the following weight components:
[0075] TPE thermoplastic elastomer: 70 parts of hydrogenated SBS, 30 parts of SEBS;
[0076] Deodorant: 12 parts of nano-activated carbon, 8 parts of natural zeolite, 6 parts of bamboo charcoal powder;
[0077] Plasticizer: 450 parts of cycloparaffin white oil;
[0078] Antioxidants: 7 parts of hindered phenol antioxidant, 5 parts of phosphite antioxidant, 3 parts of vitamin E derivative;
[0079] Light stabilizer: 5 parts of hindered amine light stabilizer, 4 parts of benzophenone ultraviolet absorber;
[0080] Calcium stearate: 20 parts;
[0081] Nano silicon dioxide: 10 parts;
[0082] Silicone modifier: 5 parts of silicone oil;
[0083] Bio-based plasticizer: 150 parts of polylactic acid-based plasticizer;
[0084] Nano titanium dioxide: 5 parts;
[0085] Graphene nanosheets: 1 part;
[0086] Metal organic framework compounds: 5 parts of iron-containing MOFs;
[0087] Carbon nanotubes: 0.5 parts;
[0088] Self-healing polymer containing microcapsules: 2 parts of shape memory polymer-based self-healing polymer;
[0089] Antibacterial agent: quaternary ammonium salt compound 10 parts;
[0090] Preparation steps:
[0091] After weighing all the raw materials according to the above ratio, place them in a high-speed mixer and mix them for 24 hours;
[0092] The uniformly mixed composite material is melt-blended through a twin-screw extruder, and the temperature of the extruder is set to 175°C;
[0093] The hot melt fluid at the outlet of the extruder is fed into an extrusion molding machine, and the extrusion molding machine extrudes the fluid into a sealing strip at 175°C;
[0094] The formed sealing strips are cooled, then cut and packaged;
[0095] The obtained sealing strip is post-processed, such as trimming, grinding, etc., to meet the requirements of the final product.
[0096] In order to verify the performance of the low-odor soft TPE composite materials prepared in Examples 1-3, the following tests were performed:
[0097] 1. Smell test
[0098] Purpose: To evaluate the odor level of composite materials and ensure their low odor properties.
[0099] Test method: According to ISO 17299-2 standard, odor test is performed on composite materials.
[0100] 2. Mechanical properties test
[0101] Purpose: To evaluate the tensile strength and elongation at break of composite materials to determine their mechanical properties.
[0102] Test method:
[0103] Tensile strength: According to ASTM D638 standard, the tensile strength of the composite material is tested.
[0104] Elongation at break: The elongation at break of the composite material was tested according to ASTM D638.
[0105] 3. Thermal stability test
[0106] Purpose: To evaluate the thermal stability and weight loss of composite materials during heating.
[0107] Test method: According to ASTM D4100 standard, thermal gravimetric analysis (TGA) was performed on the composite materials.
[0108] 4. UV stability test
[0109] Purpose: To evaluate the weathering and aging resistance of composite materials under UV irradiation.
[0110] Test method: According to ASTM G154 standard, ultraviolet accelerated aging test is performed on composite materials.
[0111] 5. Biodegradability test
[0112] Objective: To evaluate the biodegradability of bio-based plasticizers in composites to assess their environmental friendliness.
[0113] Test method: The biodegradability of bio-based plasticizers was tested according to ASTM D6400.
[0114] 6. Antibacterial performance test
[0115] Objective: To evaluate the antimicrobial effect of composite materials and ensure their hygienic properties.
[0116] Test method: According to ISO 22196 standard, the antimicrobial activity of composite materials was tested.
[0117] 7. Wear resistance test
[0118] Purpose: To evaluate the wear resistance of composite materials, which is critical to determining the durability of the material. Test method: The wear resistance of composite materials was tested according to ASTM D4060.
[0119] 8. Hardness test
[0120] Purpose: To evaluate the hardness of composite materials, which is important for understanding the physical properties of the material.
[0121] Test method: According to ASTM D2240 standard, the hardness of composite materials was tested.
[0122] 9. Chemical resistance test
[0123] Purpose: To evaluate the stability of composite materials under the action of different chemicals.
[0124] Test method: According to ASTM D543 standard, the chemical resistance of composite materials was tested.
[0125] 10. Purpose of environmental adaptability test: To evaluate the performance changes of composite materials under different environmental conditions.
[0126] Test method: According to ASTM D4329 standard, the environmental adaptability test of composite materials was carried out.
[0127] The following is a data table of performance tests based on the above three embodiments as shown in Table 1:
[0128] Table 1
[0129]
[0130] As can be seen from Table 1 above, Examples 1-3 all achieved the lowest odor level 1 in the odor test, which indicates that the prepared low-odor soft TPE composite material has a significant effect in controlling odor. This low-odor property makes the material very suitable for odor-sensitive applications, such as medical supplies and children's toys, which have strict requirements on the odor of the material.
[0131] The tensile strengths of Example 1 and Example 2 are 12.5 MPa and 13.0 MPa, respectively, while the tensile strength of Example 3 is slightly higher, reaching 14.0 MPa. These data show that the composite material has excellent mechanical strength and can remain unbroken when subjected to a certain tensile force.
[0132] The elongation at break data further confirms the material's flexibility. High elongation at break means that the material can withstand large deformations before breaking, which is very beneficial for applications that require flexibility, such as soft toys and sealing strips.
[0133] Thermogravimetric analysis (TGA) results show that all examples have relatively low weight loss percentages during heating, indicating that the composite materials have good thermal stability. This property makes the material suitable for applications that may be exposed to higher temperature environments.
[0134] The results of the UV stability test show that all examples showed no cracking or fading after the UV accelerated aging test, which indicates that the material has excellent weather resistance and UV resistance and is suitable for use in outdoor environments or applications exposed to sunlight for a long time.
[0135] The deodorant used in the present invention has the ability to effectively capture, adsorb and degrade odor molecules during the hot melting process of the TPE composite material, which further reduces the odor of the product and improves the user experience.
[0136] The addition of heat-stable antioxidants effectively inhibits degradation reactions such as breakage and cross-linking of TPE composite material molecular chains, enhances the heat resistance and oxidation resistance of the material, and reduces the odor caused by thermal oxidation.
[0137] The addition of light stabilizers improves the material's weather resistance to ambient light aging, which is essential for extending the material's service life when used outdoors.
[0138] It can be seen from the above embodiments that the deodorant of the present invention has good performance in capturing, adsorbing and degrading odor molecules generated during the hot melting process of the TPE compound material; the heat-stable antioxidant inhibits the degradation reaction performance of the molecular chain breakage, cross-linking and other degradation reactions of the TPE compound material, thereby enhancing the thermal oxidative decomposition of the compound material during the preparation process and the environmental weathering resistance, thereby preventing further odor from occurring; the light stabilizer has weathering resistance to environmental light aging of the formed product.
[0139] Therefore, the composite material formed by the compound blending of the present invention has good heat resistance, low odor, and ultraviolet weather resistance, and the processing method is as simple as the traditional process.
[0140] The present invention effectively captures, adsorbs and degrades odor molecules generated during the hot melting process by adding a new deodorant, thereby significantly reducing the odor of the product and providing a more comfortable user experience.
[0141] The invention improves the shielding effect of the material against ultraviolet rays by adding a hindered amine type light stabilizer and an ultraviolet absorber, and enhances the weather resistance and color stability of the product when used outdoors.
[0142] The bio-based plasticizer used in the present invention is biodegradable, reduces the burden on the environment, and meets the current demand for environmentally friendly materials.
[0143] The composite material of the invention maintains the excellent mechanical properties of TPE, such as high elasticity and flexibility, and at the same time improves the hardness and wear resistance of the material by adding nano silicon dioxide and graphene nano sheets.
[0144] The addition of the metal organic framework (MOFs) of the present invention provides a high specific surface area for the composite material, enhances its adsorption capacity for odor molecules and other small molecules, and further improves the performance of the material.
[0145] The composite material of the present invention maintains the processing convenience of traditional TPE materials and can be formed by existing hot-melt processing equipment without the need for additional complex processes.
[0146] Biodegradability: The results of the biodegradability test show that the bio-based plasticizers of all the examples have a high biodegradation percentage, indicating that the materials have good environmental friendliness and are helpful in reducing environmental pollution.
[0147] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the description and content of the present invention under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A low-odor soft TPE composite material, characterized in that: The composite material comprises, by weight, 50-100 parts of TPE thermoplastic elastomer, 5-20 parts of deodorant, 150-600 parts of plasticizer, 1-10 parts of antioxidant, 1-5 parts of light stabilizer, 0-20 parts of calcium stearate, 2-10 parts of nano silicon dioxide, 1-5 parts of organosilicon modifier, 50-150 parts of bio-based plasticizer, 1-5 parts of nano titanium dioxide, 0.1-1 parts of graphene nanosheets, 1-5 parts of metal organic framework compounds; 0.01-0.5 parts of carbon nanotubes, 0.5-2 parts of self-repairing polymer containing microcapsules, and 1-10 parts of antibacterial agents.
2. The low-odor soft TPE composite material according to claim 1, characterized in that: The TPE thermoplastic elastomer is selected from one or more of hydrogenated SBS, SEBS, and SEPS; The deodorant is a composite deodorant selected from one or more of nano-grade activated carbon, natural zeolite and bamboo charcoal powder.
3. The low-odor soft TPE composite material according to claim 1, characterized in that: The antioxidant is selected from one or more of the following: primary antioxidants, hindered phenol antioxidants, phosphite antioxidants, and vitamin E derivatives.
4. The low-odor soft TPE composite material according to claim 1, characterized in that: The light stabilizer is selected from one or more of hindered amine light stabilizers and benzophenone ultraviolet absorbers; and the plasticizer is cycloalkane white oil.
5. The low-odor soft TPE composite material according to claim 1, characterized in that: The organosilicon modifier is selected from one or more of polydimethylsiloxane, silicone rubber, silicone oil and silicone resin.
6. The low-odor soft TPE composite material according to claim 1, characterized in that: The bio-based plasticizer includes one or more selected from citrate plasticizers, vegetable oil-based plasticizers, polylactic acid-based plasticizers, and starch-based plasticizers.
7. The low-odor soft TPE composite material according to claim 1, characterized in that: The metal organic framework compound is selected from one or more of zinc-containing MOFs, copper-containing MOFs, iron-containing MOFs, aluminum-containing MOFs, and MOFs containing organic ligands.
8. The low-odor soft TPE composite material according to claim 1, characterized in that: The self-healing polymer containing microcapsules is selected from one or more of thermosetting resin-based self-healing polymers, thermoplastic plastic-based self-healing polymers, shape memory polymer-based self-healing polymers, hydrogel-based self-healing polymers, photosensitive self-healing polymers, magnetosensitive self-healing polymers, pH-sensitive self-healing polymers, enzyme-catalyzed self-healing polymers, microvascular network self-healing polymers, and multilayer microcapsule self-healing polymers.
9. The low-odor soft TPE composite material according to claim 1, characterized in that: The antibacterial agent is selected from one or more of silver ion compounds, copper ion compounds, zinc ion compounds, quaternary ammonium salt compounds, nano silver particles, and natural antibacterial agents, wherein the natural antibacterial agent is selected from tea tree oil or lavender oil.
10. A method for preparing the low-odor soft TPE composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: Place TPE thermoplastic elastomer, deodorant, antioxidant, light stabilizer, calcium stearate, nano-silicon dioxide, silicone modifier, bio-based plasticizer, nano-titanium dioxide, graphene nanosheets, metal organic framework, carbon nanotube, self-healing polymer containing microcapsules and antibacterial agent in a container, add plasticizer, fully soak and swell for 24 hours; stir and blend evenly to obtain a composite material; pass the obtained composite material through an extruder or injection molding machine at 140-200°C to make a hot-melt fluid, and send it into a molding cavity, and obtain a substrate or a product after cooling.
Citation Information
Cited By
Wear-resistant and high-temperature-aging-resistant cable material for robot as well as preparation method and application of cable material
CN120209486A
Robot wear-resistant high-temperature aging cable material and its preparation method and application
CN120209486B